Therapeutic Effects of Berberine on Liver Fibrosis are associated With Lipid Metabolism and Intestinal Flora - Liu, Xianzhi; Wang, Lifu; Tan, Siwei; Chen, Zebin; Wu, Bin; Wu, Xiaoying (Frontiers in Pharmacology, 2022)
Liver cirrhosis is a form of liver fibrosis resulting from chronic hepatitis caused by various liver diseases, such as viral hepatitis, alcoholic liver damage, nonalcoholic steatohepatitis, autoimmune liver disease, and by parasitic diseases such as schistosomiasis. Liver fibrosis is the common pathological base and precursors of cirrhosis. Inflammation and disorders of lipid metabolism are key drivers in liver fibrosis. Studies have determined that parts of the arachidonic acid pathway, such as its metabolic enzymes and biologically active products, are hallmarks of inflammation, and that aberrant peroxisome proliferator-activated receptor gamma (PPARγ)-mediated regulation causes disorders of lipid metabolism. However, despite the ongoing research focus on delineating the mechanisms of liver fibrosis that underpin various chronic liver diseases, effective clinical treatments have yet to be developed. Berberine (BBR) is an isoquinoline alkaloid with multiple biological activities, such as anti-inflammatory, anti-bacterial, anti-cancer, and anti-hyperlipidemic activities. Many studies have also found that BBR acts via multiple pathways to alleviate liver fibrosis. Furthermore, the absorption of BBR is increased by nitroreductase-containing intestinal flora, and is strengthened via crosstalk with bile acid metabolism. This improves the oral bioavailability of BBR, thereby enhancing its clinical utility. The production of butyrate by intestinal anaerobic bacteria is dramatically increased by BBR, thereby amplifying butyrate-mediated alleviation of liver fibrosis. In this review, we discuss the effects of BBR on liver fibrosis and lipid metabolism, particularly the metabolism of arachidonic acid, and highlight the potential mechanisms by which BBR relieves liver fibrosis through lipid metabolism related and intestinal flora related pathways. We hope that this review will provide insights on the BBR-based treatment of liver cirrhosis and related research in this area, and we encourage further studies that increase the ability of BBR to enhance liver health.